Answer :
Answer:
x= -8
Step-by-step explanation:
x-89=7(2x+3)-6 distribute 7
x-89=14x+21-6 add like terms
-13x=104 divide
x=-8
Answer: [tex]x=-8[/tex]
Simplify both sides of the equation
[tex]x+-89=(7)(2x)+(7)(3)+-6(Distribute)\\x+-89=14x+21+-6[/tex]
[tex]x-89=(14x)+(21+-6)[/tex] (Combine Like Terms)
[tex]x-89=14x+15[/tex]
Subtract 14x from both sides
[tex]x-89-14x=14x+15-14x\\-13x-89=15[/tex]
Add 89 to both sides
[tex]-13x-89+89=15+89\\-13x=104[/tex]
Divide both sides by -13
[tex]-13x/-13=104/-13\\x=-8[/tex]